Analysis Of Student’s Mathematical Communication Ability Through A Realistic Learning Approach Based On Gender At Smpn 3 Satu Atap Silangkitang - Ulfa Dinata Damanik; Hasratuddin Hasratuddin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to analyze learning with a Realistic Mathematics Approach to the mathematical communication abilities of Grade VIII students and studied based on gender which was carried out at SMP Negeri 3 Silangkitang. This research is a quantitative study using the Two Ways Anova test to see the effect of learning variables and gender on students' mathematical communication abilities, as well as to see the interactions between the three variables. This research was conducted for 5 meetings which included pretest and posttest. . The two-way Anava analysis shows that the Realistic Mathematics Approach has a positive and significant effect on students' mathematical communication skills compared to the usual learning approach and there is no interaction between learning and gender on students' mathematical communication abilities.